Antecedents influencing parents' decisions in selecting higher education institutions - Mohd Radzol, Aifa Rozaini; Teoh, Kenny Guan Cheng; Hashim, Haslinda; Ismail, Noor Azlin (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This study examines the factors that influence parent intention in selecting Private Universities for their children. Purposive sampling was used for the study. Target respondents were parents who have the intention to enroll their children into Private Universities in the Klang Valley, Malaysia. This research surveyed 394 respondents during various education fairs and private university open days. Underpinned by Consumer Satisfaction Theory (Oliver, 1980) this study adopts Brand Equity, Involvement, Advertising, Satisfaction and Purchase Intention as the research constructs in the research framework; and examines the relationships between Brand Equity, Involvement and Advertising to Satisfaction; and Satisfaction to Intention. This study also investigates the mediating effect of Satisfaction. Using PLS-SEM to analyze the data, seven hypotheses are proposed and supported by the results. They offer insights into how parents select Private Universities for their children; and should be useful to Private Universities for developing enrolment strategies.